Psikoedukasi Mengenai Musyawarah Mufakat sebagai Perwujudan Demokrasi Pancasila pada Siswa di SMP Mardi Waluya - Kristy, Ellena; Grace, Viona; Helga, Patricia; Lovela, Adelia; Silviana, Silviana; Tumanggor, Raja Oloan (Lembaga Yasin AlSys, 2024)
The Community Service (PKM) activity held at SMP Mardi Waluya Cibinong on November 22, 2024 aims to provide education on consensus as a manifestation of Pancasila Democracy in the school environment. This activity was attended by 206 grade VIII students divided into five groups. The method used in this activity is psychoeducation, which involves presentation techniques, group discussions, and interactive games. The activity began with a presentation of material on the importance of the value of consensus in everyday life, followed by a group discussion session to hone communication and tolerance skills. In closing, the interactive game session tested students' understanding of the concept of consensus. The results of this activity show that psychoeducation succeeded in introducing the concept of consensus in a practical and interesting way, as well as providing students with a better understanding of the application of Pancasila values ​​in everyday life, especially in the school environment. Through this activity, it is expected that students can internalize the value of consensus and make it a part of their attitudes and behavior in their social life.